BAF chromatin remodeling complex: Cortical size regulation and beyond - Tuoc, Tran Cong (Landes Bioscience, 2013)
The multi-subunit chromatin remodeling BAF complex controls different developmental processes. Using cortex-specific conditional knockout and overexpression mouse models, we have recently reported that BAF170, a subunit of the vertebrate BAF chromatin remodeling complex, interacts with transcription factor (TF) Pax6 to control cortical size and volume. The mechanistic basis includes suppression of the expression of Pax6 target genes, which are required for genesis of cortical intermediate progenitors (IPs) and specification of late neuronal subtype identity. In addition, we showed that a dynamic competition between BAF170 and BAF155 subunits within the BAF complex during progression of neurogenesis is a primary event in modulating the size of the mammalian cortex. Here, we present additional insights into the interaction between the BAF complex and TF Pax6 in the genesis of IPs of the developing cortex. Furthermore, we show that such competition between BAF170 and BAF155 is involved as well in the determination of the size of the embryonic body. Our results add new insights into a cell-intrinsic mechanism, mediated by the chromatin remodeling BAF complex that controls vertebrate body shape and size.